2023
DOI: 10.1039/d2cp04456k
|View full text |Cite
|
Sign up to set email alerts
|

The van der Waals interactions in systems involving superheavy elements: the case of oganesson (Z = 118)

Abstract: This work presents a study involving dimers composed of He, Ne, Ar, Kr, Xe, Rn, and Og noble gases with the Oganesson, a super-heavy closed-shell element (Z=118). The He-Og, Ne-Og,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Interested readers may want to look at theoretical modeling developments in this area, including in superheavy elements (Z Z 104), to become more familiar with them. [137][138][139] Since this problem is not purely of nuclear physics, consideration of the interaction of radioactive materials and surface physics are lacking. Studies on the adsorption coverage on the AuNPs are few, as well as the issue of combining two vastly different energy regimes between the adsorption process (on the order of eV) and the decay process (on the order of MeV).…”
Section: Theoretical Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interested readers may want to look at theoretical modeling developments in this area, including in superheavy elements (Z Z 104), to become more familiar with them. [137][138][139] Since this problem is not purely of nuclear physics, consideration of the interaction of radioactive materials and surface physics are lacking. Studies on the adsorption coverage on the AuNPs are few, as well as the issue of combining two vastly different energy regimes between the adsorption process (on the order of eV) and the decay process (on the order of MeV).…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…Interested readers may want to look at theoretical modeling developments in this area, including in superheavy elements ( Z ≥ 104), to become more familiar with them. 137–139…”
Section: Issues To Be Tackledmentioning
confidence: 99%
“…Let us mention some of these theoretical studies, to illustrate the interesting chemistry (and physics) that might be found with these SHEs. Indeed, the chemical behaviour of two SHEs has been found to differ from what was previously expected from them: copernicium, Cn (Z=112) [25][26][27][28][29][30] and oganesson, Og (Z=118) [31,28,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Og(𝑍=118) appears to form charged hydrides, fluorides and diatomic molecules with itself under various environmental conditions, making this element attractive for its high reactivity relative to the other noble gases. [31,28,[32][33][34]36].…”
Section: Introductionmentioning
confidence: 99%